2017
DOI: 10.1007/s11266-017-9909-2
|View full text |Cite
|
Sign up to set email alerts
|

Volunteer Reliability in Nonprofit Organizations: A Theoretical Model

Abstract: General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights.• Users may download and print one copy of any publication from the public portal for the purpose of private study or research. • You may not further distribute the material or use it for any profit-making activity or commer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 87 publications
0
8
0
1
Order By: Relevance
“…Our study has furthermore shown that in the specific case of stereotypes, the NPOs' professionalization scale highlighted some organizational conditions of volunteers' negative stereotyping (i.e., considering volunteers to be cold). More generally, the professionalization scale could help scholars to better understand perceptions of NPOs' professionalization and potentially its consequences for reliability (Vantilborgh & Van Puyvelde, 2017), turnover intentions (Ferreira et al, 2015) and the like, among volunteers and paid employees. In particular, future research should investigate how to buffer the negative consequences of professionalization, while maintaining the emphasis on its positive influences (Vantilborgh et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study has furthermore shown that in the specific case of stereotypes, the NPOs' professionalization scale highlighted some organizational conditions of volunteers' negative stereotyping (i.e., considering volunteers to be cold). More generally, the professionalization scale could help scholars to better understand perceptions of NPOs' professionalization and potentially its consequences for reliability (Vantilborgh & Van Puyvelde, 2017), turnover intentions (Ferreira et al, 2015) and the like, among volunteers and paid employees. In particular, future research should investigate how to buffer the negative consequences of professionalization, while maintaining the emphasis on its positive influences (Vantilborgh et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In doing so, we are making a significant contribution to the literature on social perceptions of volunteering (Ho & O'Donohoe, 2014). We are also responding to the call of authors such as Vantilborgh et al (2011), Vantilborgh and Van Puyvelde (2017), and Alfes, Antunes, and Shantz (2017) for research exploring the consequences of NPOs' professionalization. In addition, we use a quantitative measure of professionalization that can be helpful to the nonprofit research community.…”
mentioning
confidence: 99%
“…Yet, using again indications from SET, positive relationships among members of an organization will make individuals more inclined to remain in organizations (Yang et al , 2011). This situation is particularly true for those organizations where there is a need for strong commitment (Clary et al , 1998; Omoto and Snyder, 1995) and intense and reciprocal social relations, as those using volunteers (Vantilborgh and Van Puyvelde, 2018; Webb et al , 2000; Wilson, 2000). Moreover, if the norm of positive reciprocity is widespread within the organization, volunteers and managers will be more inclined to feel social integration and a sense of belonging (Molm et al , 2007), so increasing their intention to stay within the organization (Mitchell et al , 2001).…”
Section: Theoretical Framework and Hypothesesmentioning
confidence: 99%
“…Relawan yang engaged dengan perannya akan merasakan kepuasan atas pengalamannya dan rendahnya intensi untuk meninggalkan organisasi (Huynh, Xanthopoulou, & Winefield, 2014). Sedangkan relawan yang memiliki work engagement rendah atau disengagement juga menyebabkan dampak negatif bagi organisasi non-profit diantaranya organisasi non-profit akan mengalami gangguan dalam mencapai misinya (Vantilborgh & Puyvelde , 2017), menunjukkan perilaku kontraproduktif seperti tidak bertanggung jawab dengan pekerjaan, melakukan pekerjaan dengan jumlah minimum, kualitas pekerjaan yang buruk, melakukan pencurian, konflik dengan partner kerjanya (Myers, 2014). Relawan yang disengaged dengan pekerjaannya akan meninggalkan organisasi dan menyebabkan ketidakefisienan dalam organisasi.…”
Section: P E N D a H U L U A Nunclassified